Adsorption of bovine serum albumin onto immobilized cobalt microporous and mesoporous silica adsorbents [electronic resource] - Siti Hasmah Hussin, 1986- author; Siti Hamidah Mohd. Setapar, supervisor; Fakulti Kejuruteraan Kimia (2013)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2013